2008
DOI: 10.1016/j.bbamcr.2007.11.017
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α controls keratinocyte proliferation by up-regulating p21(WAF1/Cip1)

Abstract: The cyclin-dependent kinase inhibitor p21(WAF1/Cip1) plays a central role in a spatial and temporal balance of epidermal keratinocyte proliferation and growth arrest. However, what controls p21 expression in keratinocytes remains uncertain. Hypoxia-inducible factor 1alpha (HIF-1alpha) does not only express a variety of genes essential for hypoxic adaptation, but also up-regulates p21 so as to slow down cell cycle under hypoxic conditions. In the present study, we examined the role of HIF-1alpha in p21-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 34 publications
2
50
1
Order By: Relevance
“…This is most probably due to the well-recognized negative feedback regulation by Smad7 (Ten Dijke et al, 2002), which was detected in the gene expression array. Furthermore, p21CIP expression in keratinocytes in vitro was reported to be strongly upregulated in response to increasing cell density (Cho et al, 2008). Due to the severe growth defect of N-WASP keratinocytes in vitro, the cell density for control and mutant keratinocytes was rather different throughout the experiments and the higher density of control cells could have increased their p21CIP expression.…”
Section: Differential Keratinocyte Gene Expression In the Absence Of mentioning
confidence: 99%
“…This is most probably due to the well-recognized negative feedback regulation by Smad7 (Ten Dijke et al, 2002), which was detected in the gene expression array. Furthermore, p21CIP expression in keratinocytes in vitro was reported to be strongly upregulated in response to increasing cell density (Cho et al, 2008). Due to the severe growth defect of N-WASP keratinocytes in vitro, the cell density for control and mutant keratinocytes was rather different throughout the experiments and the higher density of control cells could have increased their p21CIP expression.…”
Section: Differential Keratinocyte Gene Expression In the Absence Of mentioning
confidence: 99%
“…Several lines of evidence suggest that the expression of HIF-1a by skin cells control the response of the organism to oxygen, and can play a major role in skin homeostasis (Cho et al, 2008;Liu et al, 2008;Michaylira and Nakagawa, 2006;Rezvani et al, 2011a). Epidermis and adnexae constitutionally express HIF-1a (Bedogni et al, 2005;Distler et al, 2004;Rosenberger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, we previously found that epidermal keratinocytes uniquely express substantial amounts of HIF-1α even in normoxia. We also demonstrated that mitochondrial reactive oxygen species and the MEK/ERK pathway are involved in HIF-1α stabilization in keratinocytes [9]. In another study, we showed that UVB down-regulates HIF-1α by inhibiting the cap-dependent translation of HIF-1α [10].…”
Section: Discussionmentioning
confidence: 83%
“…We previously demonstrated that HIF-1α induces cell cycle arrest in keratinocytes by inducing p21 [9]. Thus, we examined whether Py-Zn induced p21 through HIF-1α ex- pression in keratinocytes, and found such an effect by Py-Zn (Fig.…”
Section: Pyrithione-zinc Induces P21 In Uvb-irradiated Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation